Retail Strategies of Nottingham Forest Football Club - A Look at the impact of Marketing Communication for the improvement of the retail channels of Nottingham Forest - Vig, Tarun (2008)
As a football fan and also a business student pursuing MBA with particular interest in retail strategy, especially marketing communications and promotions, the opportunity to work with Nottingham Forest was the perfect opportunity.Nottingham Forest Football Club is deeply concerned with the level of sales and revenue it makes from merchandise sales, across their retail channels. In tackling this issue, it was important to understand the shift in football from being just about entertainment but more about a business which not only pays for itself but also makes profit. Key to this shift is the knowledge that although football's (and sports in general) offering is intangible (i.e. it provides entertainment and a sense of belonging and attachment), it is this very intangibility that provides the basis for tangible cues. The success of these tangible cues is dependent on the value attached to the club by the fans; that is, the loyalty of the fans to the brand.It was also pertinent to note that in retailing, marketing communications and promotions play a very big role in helping organizations achieve their goals. Understanding customers is essential in helping them in making the correct choice. Having a perfect mix of marketing communication strategies is essential to reach out to different groups of customers. The research process included interviews and questionnaires. On the part of the questionnaires, the sample group used, although highlighting trends in direction and thought, may actually not be enough to determine if the views were an adequate representation of the whole fans. Also, there might be some biases on both the parts of the interviewer and interviewee. The research was able to locate areas that needed addressing. The most important being the lack of effective use of marketing communications and promotional strategies. Some recommendations which should help in improving the sales and revenue of the club have been made based on the research. Also, this research is for the use of Nottingham Forest Football Club though it may also prove helpful to other clubs.